Las prácticas curriculares y extracurriculares realizadas por los estudiantes de la facultad de documentación de la universidad de Murcia (1991-2001) - Chain Navarro, Celia; Garrido Lova, Josefina; López Lucas, Encarni; Martínez Pellicer, Antonia (Revista General de Información y Documentación, 2002)
The present study analyses the sessions of practical work carried out by students on the diploma course in Librarianship and on the course for the Licenciate in Information Science at the University of Murcia from their beginnings in 1991 up to 2001. A quantitative analysis of information drawn from the data base belonging to the Centre for Employment Orientation and Information (COIE) is carried out detailing the centers for the practical sessions, towns, duration, grants. etc. Afterwards the information contained in the reports submitted on completion of the practice is analyzed with a view to obtaining the functions and profiles most required by companies. The functions most in demand are those which are traditionally recognized as belonging to the profession such as cataloguing and classification of documents, although there is a trend towards other more up to date activities such as the setting up and updating of databases, Internet searching, audiovisual resources management and quality management. This is particularly significant in the practices for the Licentiate in Documentation. The grants, although an important incentive, do not cover even 24% of the practices carried out by students following the diploma course whereas they cover more than 50% of those in the second cycle. The analysis of the practices for both the diploma and the licentiate evidences similar characteristics with a few changes in the functions required. It also reveals that organizations when asking for students require the same profiles both for the first and the second cycle which would seem to indicate that they are not very clear as to the difference between the two.
Keywords: Practicum; University; Librarianship; Information Science; Core curriculum; COIE; Centre for Employment Orientation and Information; Employment; Curriculum